Chl a fluorescence and proteomics reveal protection of the photosynthetic apparatus to dehydration in tolerant but not in susceptible wheat cultivars - M. Nykiel; P. Lisik; J. Dębski; B. Florea; K. Rybka (Biologia Plantarum, 2019)
Seedlings of spring wheat (Triticum aestivum L.) cultivars, Ethos and Zebra, differing in drought tolerance were dehydrated to reach a water saturation deficit (WSD) in leaves ~15, 30, and 50 %. Ethos, the drought tolerant cultivar, dried slower in comparison with Zebra and regrew in 70 % upon rehydration. The effect of dehydration on photosystem II was evaluated by Chl a fluorescence (OJIP transients). The inflection point of double normalized curves (ΔWOJ) calculated for Ethos was negative for seedlings with 15 % WSD, nearly zero for those with 30 % WSD, and about +0.05 for those with 50 % WSD. In case of Zebra, the 15 % WSD already induced a positive ΔWOJ (+0.05) and 50 % WSD maximized it to +0.10, which is a sign of drought susceptibility. The proteomic studies revealed, that among identified 850 spots, 80 protein spots were differentially expressed during dehydration. The differentially expressed proteins of the drought tolerant cultivar indicated the protection of the photosynthetic apparatus and proteome rebuilding in response to drought. In the drought susceptible cultivar, protection of proteins and membranes and partial scavenging reactive oxygen species appeared.